2000
DOI: 10.1136/ip.6.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Increasing age and experience: are both protective against motorcycle injury? A case-control study

Abstract: Objectives-To assess the associations between age, experience, and motorcycle injury. Setting-Motorcycle riding on nonresidential roads between 6 am and midnight over a three year period from February 1993 in Auckland, New Zealand. Methods-A population based casecontrol study was conducted. Cases were 490 motorcycle drivers involved in a crash and controls were 1518 drivers identified at random roadside surveys. Crash involvement was defined in terms of a motorcycle crash resulting in either a driver or pillio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 5 publications
6
53
1
8
Order By: Relevance
“…In common with the majority of studies, we identified an excess risk of accident involvement among novice PTW riders (Chang and Yeh 2006;Evans 2004;Harrison and Christie 2005;Lardelli-Claret et al 2005;Lin et al 2003;Mullin et al 2000;Reeder et al 1995;Rutter and Quine 1996;Ryan et al 1998;Skalkidou et al 1999;Yannis et al 2005). This may be due to a combination of young people's inexperience and risk-taking (Chesham et al 1993;Ryan et al 1998) as well as risk exposure (Harrison and Christie 2005;Yannis et al 2005).…”
Section: Discussionmentioning
confidence: 81%
“…In common with the majority of studies, we identified an excess risk of accident involvement among novice PTW riders (Chang and Yeh 2006;Evans 2004;Harrison and Christie 2005;Lardelli-Claret et al 2005;Lin et al 2003;Mullin et al 2000;Reeder et al 1995;Rutter and Quine 1996;Ryan et al 1998;Skalkidou et al 1999;Yannis et al 2005). This may be due to a combination of young people's inexperience and risk-taking (Chesham et al 1993;Ryan et al 1998) as well as risk exposure (Harrison and Christie 2005;Yannis et al 2005).…”
Section: Discussionmentioning
confidence: 81%
“…A survey of adult Queensland cyclists found that 26% of respondents had only been riding regularly in the last two years (Haworth and Schramm, 2011). Inexperience has also been shown to be a major factor in motorcycle crashes (Mullin et al, 2000;Rutter and Quine, 1996). Inexperience appears to contribute to crash risk by means of lower levels of vehicle control skill and lower levels of hazard perception and responding (Bellet and Banet, 2012;Habibovic and Davidsson, 2012;Hosking et al, 2010), both leading to poorer ability to avoid crashes.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies driver inexperience with motorcycle riding has been shown to be a risk factor for motorcycle collisions. 15,16 Research on licensing programmes for motorcyclists suggests that specific restrictions, such as being under adult supervision, driving only in daylight and enforcement of a zero blood-alcohol level tolerance limit, are factors associated with a reduced number of collisions. 17 A direct association between motorcycle sales and mortality rates has been reported previously.…”
Section: Research Motorcycle Driving Requirements and Traffic Injuriementioning
confidence: 99%